DEVELOPMENT OF FLASHCARD MEDIA BASED ON AUGMENTED REALITY TO IMPROVE THE SPEAKING ABILITY OF AUTISTIC STUDENTS AT SLB AUTIS LABORATIUM UM - Hastuti, Wiwik Dwi; Salsabila, Annisa Zahra (Indonesian Journal of Educational Development (IJED), 2024)
Autistic students experience developmental disorders that affect various aspects, namely thinking ability, socialization, communication, and behavior in accepting abstract things. Based on preliminary studies at SLB Autis Laboratorium UM, they experience limited new vocabulary that affects their speaking ability so that echolalia characteristics often appear in the learning process. In addition, the learning media used are still limited and less innovative in teaching abstract things to students. The purpose of this research is to develop learning media in the form of augmented reality-based flashcards that are effective and valid and can improve speaking skills, especially in pronouncing vocabulary and questioning activities or having simple conversations, especially for autistic students where 3D animated animal models will appear followed by audio explanations when used. This study uses a research and development method developed by ADDIE with 5 stages of development, namely (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The subjects in this research and development are media experts, material experts, practitioners, and 3 autistic students from class III. The data collection techniques used were observation, interviews, questionnaires, and documentation. The results of this study indicate that Augmented Reality-Based Flashcard media are feasible and effective in using Indonesian language learning at the UM Laboratory Autistic SLB. This is evidenced by the media validation test score of 98% and 100%, the material validation test score of 100% and 100%, and the assessment of the results of the practitioner validation test of 82% and 98%. The overall assessment of the validation test that has been carried out is 96% (Very Valid). In addition, the overall assessment of the small group trial that has been carried out is obtained at 87.5% (Highly Effective).